The Effect of Entrepreneurial Education on Internet Entrepreneurship Performance Mediated By Self-Efficacy (Empirical Study on Instagram Online Shop In Jakarta Province) - Oscar Jayanagara; Albert Dermawan Yusup (Universitas Pelita Harapan, 2025)
ABSTRACT The development of social media not only helps people in building communication but also becomes a business opportunity for internet-based entrepreneurs. However, on the other hand, the topic that discusses internet entrepreneurship is still very rarely raised. Therefore, this study was conducted to determine what factors are able to improve or influence internet entrepreneurship performance. This study is included in the type of quantitative research, with the number of samples obtained as many as 500 respondents, the data collection technique used was a questionnaire and the data analysis technique used was PLS-SEM. The results of the study showed that entrepreneurial education had a significant and positive effect on internet entrepreneurial self-efficacy and internet entrepreneurship performance, especially financial, internal and learning and growth perspectives. Internet entrepreneurial self-efficacy was also found to have a significant and positive effect on all perspectives in internet entrepreneurship performance. Then internet entrepreneurial self-efficacy also has significant mediation between the influence of entrepreneurial education on all perspectives in internet entrepreneurship performance. However, entrepreneurial education was found to have no significant effect on internet entrepreneurship performance: customer perspectives.